Theodor Adorno's epistemology : a positive interpretation - Teng, Gerald Yi Shee (Nanyang Technological University, 2021)
This paper will advance a novel interpretation of Theodor Adorno’s theory of knowledge, or epistemology, in his magnum-opus, Negative dialectics. I argue, contra the dominant interpretation of Negative Dialectics in the literature, that Adorno can be taken to propound a positive and systematic theory of knowledge despite his commitments to anti-systematicity. The paper comprises three main sections. In the first section, I argue that Adorno adopts a Kantian foundation for his epistemology. I will show that Adorno is interested in a theory of objective knowledge based on a Kantian understanding of a mediated relationship between subject and object. In the second section, I elucidate Adorno’s conception of “conceptuality” and “constellation.” I argue that Adorno posits both necessary and sufficient conditions for true objective judgements. In the third section, I attempt a systematic reconstruction of Adorno’s epistemology. I argue that Adorno’s position can be considered as an improvement over the position of epistemic contextualism in analytic epistemology. To end, I consider how Adorno’s epistemology can be read alongside his critical theory. I suggest that Adorno’s epistemology is not descriptive but normative— Adorno’s Negative Dialectics expresses an approximate, but importantly, ethically and critically informed, theory of knowledge.